The fox hunt mystery - Keene, Carolyn; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1996)
When Nancy's friend Laura's family stables are sabotaged and then Laura's favorite horse is stolen, Nancy must discover if Laura's spoiled rival is trying to hurt her or if the upcoming fox hunt has enraged animal activists who will stop at nothing to end this sport.
"A Minstrel book."
Keywords: Horses -- Fiction; Fox hunting -- Fiction; Animal rights activists -- Fiction; Mystery fiction; Young adult fiction